Other to other (O2O) : expanding successful engagement outside your comfort zone - Beverly, Cheryl L. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Other to Other (O2O): Expanding successful engagement outside your comfort zone was written by an educator for educators, and others interested in understanding and creating successful Other to Other engagements. In this book, Cheri Beverly, shares her thinking, questing, connecting, and meaning making around learning to engage with people, places, practices, ideas, etc. that are different from one's own. She builds on 43 years as an educator who has worked with learners and educators representing a range of resources, experiences, assumptions, and expectations, in a variety of learning spaces. Cheri begins by describing her journey to the O2O model. She then introduces the reader to each component of the model: knowledge, skills, personal characteristics, and motivation. After explaining each component, Cheri synthesizes them into a working model and describes how it can inform our understanding, decisions, and actions regarding engaging out of our comfort zones"-- Provided by publisher.
Keywords: Communication in education.; Intercultural communication.; Interpersonal relations.; Education -- Philosophy, Theory & Social Aspects.; Philosophy and theory of education.; elektronické knihy; electronic books